Tuning the dual emission of keto/enol forms of excited-state intramolecular proton transfer (ESIPT) emitters via intramolecular charge transfer (ICT). (September 2021) - Huang, Quan; Guo, Qiang; Lan, Jingbo; You, Jingsong
Abstract: Herein disclosed the adjustment of the dual emission of keto and enol forms of excited-state intramolecular proton transfer (ESIPT) emitters via intramolecular charge transfer (ICT) effects. Introducing electron-donating triphenylamine (TPA) and electron-withdrawing triphenylboron (TPB) substituents into the para -position of the phenolic hydroxyl group or the side of the oxazole of 2-(2′-hydroxyphenyl)oxazole skeleton endows the resulting compounds (6a -6d ) with different photophysical properties. Owing to the ICT effect from electronic donor to acceptor, introducing TPA into the side of oxazole and TPB into the para -position of phenolic hydroxyl is conducive to an enol-form emission (6a ). Exchanging the two substituents, namely introducing TPB into the side of oxazole and TPA into the para -position of phenolic hydroxyl, would be beneficial to a keto-form emission (6b ). Synchronously introducing two identical substituents, whether TPA or TPB, into two sides of 2-(2′-hydroxyphenyl)oxazole skeleton (6c and 6d ) would lead to the dual emission of keto and enol forms due to the excited-state equilibrium of ESIPT reactions, which are further verified by DFT calculation. The organic light-emitting diode (OLED) devices with 6a and 6c as emitters were fabricated, both of which exhibit hybridized local and charge transfer (HLCT) excited-state characters with high external quantum efficiencies (EQEs) of 4.9% and 5.6%, respectively. Highlights: The adjustment of keto/enol emission of ESIPT emitters was systematically investigated for the first time. ICT effect was deduced to be the main driving force to lead to the different luminescence properties of these ESIPT emitters. The excited-state equilibrium of ESIPT reactions is verified by DFT calculation. OLEDs based on ESIPT emitters exhibit high external quantum efficiencies. The HLCT characters of ESIPT emitters were confirmed by experimental data and theoretical calculations.